Malathion Resistance i n Tribolium castaneum (Coleoptera: Tenebrionida e) in Bangladesh - Talukder, Farid; Rahman, Ataur; hahjahan, Md (Biological Sciences - PJSIR, 2007)
Ma l ath ion resistance i n th e red nou r beetl e ( Tribolium castanewn H erbst) i s wid espread and stabl e i n n atural popu l ati on s even in th e ab en ce or pest i cide exposure. N i ne sampl e popu l ati on of T. astaneum collected from ni ne different si l os, centra l storage dep t s (CSD) and local storage depots (LSD) of Banglad esh , and were test ed to determi n ethei r re si stance ratio to M a l ath ion . In secti cide resi sta n ce was observed i n most of th e col l ected populations. A mon g n i ne tested population s of r ca ·taneum, th e Ghatai l LSD popu l ation devel oped the h i ghe t l evel of Malathion resist ance ratio, wh re as th e Serajganj L D p pu lation howed lowest resistance ratio at LC50 level , 72 h after th e treatment.